Macro and micronutrient deficiency in inflammatory bowel diseases - Jarmakiewicz, Sara; Piątek, Dominika; Filip, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Introduction. Inflammatory bowel disease (IBD) is group of global range inflammatory conditions. There has been a regular increase in the number of IBD cases. Patients exclude whole food groups from their diet fearing the emergence of disease symptoms or due to learning from unreliable sources. Doing so, they might deepen the already existing vitamin deficiencies which occur along with the shortage of many minerals. These deficiencies might intensify the disease process or cause a new one. The most common deficits pointed out by numerous researchers concern vitamin D, calcium, cobalamin, folic acid and iron. It is well worth introducing selenium, zinc and ascorbic acid into a diet because of their immunomodulating effect. Important aspect of the healing process is a personalized diet which is designed to compensate for, or prevent vitamin and mineral deficiencies. Aim. The purpose of the study was to review the literature about vitamin and mineral deficiency in Inflammatory Bowel Diseases. Materials and method. Analysis of literature.
Keywords: Crohn’s disease; IBD; ulcerative colitis; vitamins